2008
DOI: 10.1136/ard.2008.089367
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of psoriatic arthritis

Abstract: The recurrence risk ratio for both PsA and psoriasis is high in FDRs and siblings of patients with PsA. These results confirm that both PsA and psoriasis have a strong heritable component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 23 publications
7
94
3
4
Order By: Relevance
“…The difference of this instrument (TOPAS) in comparison with other questionnaires is that images of dactylitis and onychodystrophy included, which are much visual support for the patient and the doctor does not entrenado [18]. But as every instrument is flawed in this case it is the evaluation of the entheses, recalling that the target organ is the entesial complex (SEC) [1,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of this instrument (TOPAS) in comparison with other questionnaires is that images of dactylitis and onychodystrophy included, which are much visual support for the patient and the doctor does not entrenado [18]. But as every instrument is flawed in this case it is the evaluation of the entheses, recalling that the target organ is the entesial complex (SEC) [1,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is a progressive disease and aggressive, so that a delay in diagnosis and treatment of the disease can lead to an erosive arthropathy [1,2]. Although it is a heterogeneous disease, given by affecting skin, peripheral joints, axial involvement, the presence of autoantibodies (Ra Test, Anti CCP) even extra articular manifestations (uveitis, inflammatory bowel disease, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States approximately 56 million hours of work are lost by patients with the disease and as much as 3.2 billion dollars are spent per year with its treatment. 20 …”
Section: Impactsmentioning
confidence: 99%
“…23 Among twins, the incidence of psoriasis is 65% for monozygous twins and 30% for dizygous twins. 20 Currently, that genetic predisposition is attributed to the presence of human leukocyte antigens (HLA). Regarding psoriasis, several HLA can be associated, such as HLA-B13, HLA-B17, HLA-B37, HLA-Bw16, HLA-Bw57, and HLA-DR7.…”
Section: Genetic and Triggering Factorsmentioning
confidence: 99%
“…In most GWAS studies, study power remains limited and further work must be done. 14 ; showed that the recurrence risk ratio is increased in psoriasis and psoriatic arthritis (PsA) 15,16 ; and presented a summary of results from linkage studies in psoriasis that have identified 10 psoriasis susceptibility loci, as well as the result of a single linkage study in PsA 17,18 . He summarized association studies in psoriasis and PsA and described the largest GWAS survey in psoriasis that revealed an association with Th17 and nuclear factor-B (NF-kB) pathways, in addition to confirming the strong association with HLA-Cw6 19 .…”
Section: Non-mhc and As Susceptibilitymentioning
confidence: 99%